PHYSICALCHEMICAL AND FUNCTIONAL CHARACTERIZATION OF THREE COMMERCIAL CONCENTRATES FROM DIETARY FIBER - VALENCIA G., Francia E.; ROMÁN M., María O. (Vitae, 2009)
In Colombia there have been few studies done on the functionality of commercial extracts of micropulverized dietary fiber, this motivated the development of an experimental study that evaluated the functional properties, for the purpose of establishing adequate manipulation methodologies by including them in the development of new alimentary products that promote beneficial physiological effects. The present study aims to characterize two commercial extracts of micro- pulverized dietary fiber from wheat (375) and oat (528) and one from apple (659). The proximal composition, the total content of dietary fiber (FD), soluble (FDS), insoluble (FDI), in addition to viscosity (η), particle size, water retention capacity (CRW), swelling capacity (CS), organic molecule adsorption capacity (CAMO), and catatonic interchange capacity (CIC); indicated specific characteristics of the three concentrated fibers in the study. The fiber concentrates present significant differences among the physicalchemical and functional properties. Those with a major content of soluble fiber (375 and 528), showed lower values of CRW (3,8 and 3,9 from H2O/g from dry matter MD) and mayor values from CAMO (11,7 and 10,9 from oil/g from MD); the 375 fiber showed the most CS (7,1 g and H2O/g from MD).